Unequal causality between autoimmune thyroiditis and inflammatory bowel disease: a Mendelian randomization study - Bai, Siyang; Yu, Yunfeng; Yang, Xinyu; Hu, Gang; Wu, Jingyi; Tong, Keke; Yin, Yuman; Deng, Juan; Chen, Cong; Tan, Chuanchuan (Frontiers in Endocrinology, 2024)
Objective This study aims to analyze the causal relationship between autoimmune thyroiditis (AIT) and inflammatory bowel disease (IBD) using bidirectional Mendelian randomization (MR). Methods Single nucleotide polymorphisms were obtained from FinnGen. Exposure-outcome causality was assessed using inverse variance weighted, MR-Egger, and weighted median. MR-Egger intercept, Cochran’s Q, and leave-one-out sensitivity analysis were used to evaluate horizontal pleiotropy, heterogeneity, and robustness, respectively. Results Forward analysis revealed no significant association between AIT and the risk of ulcerative colitis (UC) (odds ratio [OR] 1.008, 95% confidence interval [CI] 0.986 to 1.03, p = 0.460) or Crohn’s disease (CD) (OR 0.972, 95% CI 0.935 to 1.010, p = 0.143). Reverse analysis showed that UC (OR 0.961, 95% CI 0.783 to 1.180, p = 0.707) was not associated with AIT risk, while CD (OR 2.371, 95% CI 1.526 to 3.683, p < 0.001) was linked to an increased risk of AIT. Intercept analysis and Cochran’s Q test indicated no horizontal pleiotropy or heterogeneity. Sensitivity analysis confirmed the robustness of the MR results. Conclusion This MR analysis suggests that CD, but not UC, is a risk factor for AIT, whereas AIT is not associated with the risk of IBD. Proactive prevention and treatment of CD can help mitigate the risk of AIT.